MULLIGAN BENT LEG RAISE LEBIH MENINGKATKAN LINGKUP GERAK SENDI LUMBOSAKRAL DAN MENURUNKAN DISABILITAS DIBANDINGKAN DENGAN SLUMP STRETCHING PADA PENGRAJIN GENTENG DENGAN MECHANICAL LOW BACK PAIN DI DESA DARMASABA - Prianthara, I Made Dhita; Jawi, I Made; -, Wahyuddin; Sandi, I Nengah; Griadhi, I Putu Adiartha; Munawaroh, Muthiah (Sport and Fitness Journal; Volume 5, No.3, 2017DO - 10.24843/spj.2017.v05.i03.p04, 2017)
Background: Mechanical low back pain is pain that resulting from poor posture which cause decreased disability and limitation of lumbar range of motion. Purpose: The purpose of this study was to prove mulligan bent leg raise more effective to increase lumbosacral range of motion and decreased disability than slump stretching among tile craftsman with Mechanical low back pain in Darmasaba village. Methods: This research was an experimental study with pre and post test control group design. Sample of this study is tile craftsman with mechanical low back pain with 20 samples aged 30-55. Samples were divided into two groups, which the first group (n = 10) was given Mulligan bent leg raise, while the second group was given slump stretching. Do exercise 3 times a week for 4 weeks. Lumbar range of motion was measured with modified-modified schober test while level of disability was measured with modified oswestry disability index. Result: Paired Sample T-test in Group 1 and Group 2 obtained p=0,000 that showed in each Group 1 and Group 2 there is significant difference. Independent Samples Test of Group 1 and Group 2 showed the result p=0,000 which mean that there is significant difference in increased lumbar range of motion and decreased disability. Conclusion: Mulligan bent leg raise more effective to increase lumbosacral range of motion and decreased disability than slump stretching to tile craftsman with mechanical low back pain in Darmasaba village.